Peran Zakat Mal dalam Meningkatkan Perekonomian Masyarakat dan Mengentaskan Kemiskinan - Mardhiyah, Umi Rossy (Journal of Industrial and Syariah Economics, 2024)
Zakat is a series of pillars of Islam that are mandatory for every Muslim. Zakat is a very urgent medium of worship, not just an obligation for Muslims and Muslim women, but the definition of the word urgent in worship itself has a very universal description. Through good zakat management, it is hoped that it can help meet the basic needs of the poor and encourage them to be economically independent. The research method used is descriptive qualitative, with data collection from various primary and secondary sources. The research results show that zakat has great potential in improving the community's economy, reducing poverty rates, and creating jobs. However, there are still obstacles in implementing zakat, such as lack of information and public awareness. Therefore, collaborative efforts are needed between the government, zakat institutions and the community to maximize the potential of zakat in achieving better social welfare.